(3UGdhf GdfMJ GdGhd ddNGeGJ GdfHjdI s The Premier of Sculputure Salon of Nobel Materials - (3UGdhf GdfMJ ddNGeGJ GdfHjdI s 2005 : (3GdbGgQI(B) s; (3eUQ(B.s (3hRGQI GdKbGaI (B.s (3bWGY Gdafhf GdJTcjdjIs ((3GdbGgQI (B:s (3hRGQI GdKbGaI ;s, 2005)
(3JJfGhd GGdGSWhGfI YQV JaUjdi dUGdhf GdfMJ GdGhd GdPi Gbje ai GdaJQI ef (B16 (3GHQjd Gd (B16 (3eGjh (B2005 s
(3GdLeghQ GdYGes
(3eJWdHGJ GdJTZjd (B: (3LgGR ceHjhJQ (B(pentium) (3eJhGab eY (BIbm: (3eTZd GbQGU djRQ (BCD-ROM (3SQYJI (Bx 40 (3TGTI ObI (B800 x 600 (3; (Bwindows 98/ME/XP: 64 (3ejLGHJ(B: (3cGQJ TGTI (B24 (3HJ h cGQJ UhJ (B+ (3SeGYGJ(B. s
Keywords: (3Gdafhf GdJTcjdjIs